2017
DOI: 10.1002/ehf2.12179
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact of intravenous iron therapy with ferric carboxymaltose in patients with chronic heart failure and iron deficiency in Germany

Abstract: AimsTreatment of iron deficiency (ID) in patients with heart failure (HF) with intravenous iron substitution [ferric carboxymaltose (FCM)] has previously shown significant improvements in exercise capacity, New York Heart Association (NYHA) functional class, quality of life, and reduction of hospitalization. The aim of this study was to estimate the budget impact of FCM treatment for patients with HF and ID.Methods and resultsIndividual patient data from four double‐blind randomized controlled trials were pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
(35 reference statements)
2
35
0
1
Order By: Relevance
“…In the base case analysis, FCM use is predicted to be cost saving over 5 years of treatment (€À0.8m). The German budget impact analysis, 19 based on the same pooled RCT data, compared treatment with FCM for all patients vs. no iron treatment, using 1000 patients in each group, from the perspective of the German national health insurance over a 1 year period. It concluded that in the first year, FCM was cost saving (€À198 768) if the dose of FCM was 925 mg and had a limited positive impact if the dose of 1679 mg was used (€40 031).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the base case analysis, FCM use is predicted to be cost saving over 5 years of treatment (€À0.8m). The German budget impact analysis, 19 based on the same pooled RCT data, compared treatment with FCM for all patients vs. no iron treatment, using 1000 patients in each group, from the perspective of the German national health insurance over a 1 year period. It concluded that in the first year, FCM was cost saving (€À198 768) if the dose of FCM was 925 mg and had a limited positive impact if the dose of 1679 mg was used (€40 031).…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the budget impact of FCM treatment, we adapted a decision analytic model previously used to assess the budget impact of FCM in Germany, 19 to the French setting. The adaptation was made to meet the French guidelines on budget impact analysis from the national health authorities (Haute Autorité de Santé).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations